Early Land Plants Today: Index of Liverwort and Hornwort names published 2017–2018 - Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2020)
A widely accessible list of known plant species is a fundamental requirement for global biodiversity conservation targets. An index of published names of liverworts and hornworts between 2017 and 2018 is provided as part of a community effort in working toward maintaining an updated world checklist of these groups. The list herein includes 23 higher taxon names, 143 specific names, 21 infraspecific names, one infrageneric autonym and 13 infraspecific autonyms for 2017 and 2018, including also names of fossils and invalid and illegitimate names. Sixteen older names omitted in the earlier indices are included.